Hubungan Conscientiousness dengan Pertimbangan Protokol Kesehatan dalam Perilaku Konsumsi selama Pandemi Covid-19 - Liroy Rubianto; Alexandrina J. Nathania; Gisela A. Prawesthy; Jessica -; Hanarolisa Mutalim; Immanuel Yosua; Rayini Dahesihsari (MANASA, 2021)
The Covid-19 pandemic is a major problem that is currently faced worldwide. As an effort to minimize this problem, the government enforces a health protocol appeal for the Indonesian citizens. The change in the situation affects people’s lives, especially in the economic and trade sector in Indonesia. One of the impacts is a change in people’s assumptions in assessing a product. Currently, health protocols are one of the considerations in consuming products during the pandemic, so that people move to products that can protect themselves from the transmission of Covid-19. The changes in consumer behavior can be explained through one of the dimensions of the Big Five Personality, namely conscientiousness. Conscientiousness can describe individual behavior in maintaining their own health. Therefore, this study wants to see whether there is a relationship between the conscientiousness and the consideration of health protocols in product consumption during the Covid-19 pandemic. This study uses a quantitative approach, with correlational research design. Based on the results of data analysis using Spearman’s Rank Order Correlation, the value obtained was ???????? (1056) = 0.256, p < 0.001. Therefore, it can be concluded that there is a significant relationship between conscientiousness and the consideration of health protocols in product consumption during pandemic.